The symmetric effects of inflation, exchange rates, and international trade on Indonesia's balance of payments 2015-2024 based on ARDL - Setianingrum, Dyah Ayu; Angellita, Rachel Dwitya; Pamungkas, Priyagung Jati; Firdaus, Anzar Alfat; Gunawan, Ratna Setyawati (Privietlab, 2026)
This research utilizes the Autoregressive Distributed Lag (ARDL) approach to examine the symmetrical effects of inflation, exchange rates, and international trade on Indonesia's balance of payments over the period from 2015 to 2024. Amidst global economic instability, exacerbated by the US-China trade war, the persistent pandemic COVID-19, and ongoing geopolitical tensions, the Republic of Indonesia faces significant challenges in maintaining its external balance. This study employs quarterly time series secondary data sourced from Bank Indonesia, Statistics Indonesia (BPS), and the Ministry of Trade. The long-run estimation results indicate a negative correlation between inflation and the balance of payments, with a coefficient of -3468.811 (p=0.059). This means that if inflation goes up a lot, it could make the country's external position worse. The export coefficient, at 2.4342 (p=0.000), indicates a substantial positive impact, whereas the import coefficient, at -2.5669 (p=0.000), signifies a considerable negative effect. The exchange rate's long-term influence appears relatively weak, as evidenced by a coefficient of -0.635 (p=0.082). Short-run estimations reveal that the error correction term (ECT) coefficient is -0.9766 (p=0.000), suggesting a rapid convergence towards long-run equilibrium. These findings carry significant implications for Indonesian economic policy, particularly concerning inflation control and export promotion, both of which are essential for maintaining external stability. Consequently, to enhance the long-term balance of payments, the implementation of prudent monetary and trade policies that foster export expansion while managing import levels is crucial.